Computer Modelling for Nutritionists - Mc Auley, Mark Tomás (Springer International Publishing : Imprint: Springer, 2019)
This book draws on Mark Mc Auley's wealth of experience to provide an intuitive step-by-step guide to the modelling process. It also provides case studies detailing the creation of biological process models. Mark Mc Auley has over 15 years' experience of applying computing to challenges in bioscience. Currently he is employed as a Senior Lecturer in Chemical Engineering at the University of Chester. He has published widely on the use of computer modelling in nutrition and uses computer modelling to both enhance and enrich the learning experience of the students that he teaches. He has taught computer modelling to individuals at a wide variety of levels and from different backgrounds, from undergraduate nutrition students to PhD and medical students.